KOMUNIKASI DALAM HUBUNGAN AKRAB BERDASARKAN PERSPEKTIF MANAJEMEN KOORDINASI MAKNA - Titih Nurhaipah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2019)
The communication aims to equalize the meaning. The process of interaction with the external world that is present through communication can allow people to understand their environment. The activities of daily communication will develop a meaning from the social reality created by each individual. But the meaning that is constructed from this social reality is not easily understood. There are levels or levels in the meaning of words in the socialization of life. The individual relationships will reflect the interactions through the communication made. However, the meaning built by social reality will have nothing in common. Under these conditions, it can be evaluated on the basis of the theory of the coordination of meaning management, which refers to the way in which individuals establish rules to create and interpret meanings and how these rules are intertwined in a conversation in the that the meaning is always coordinated in a relationship Keyword: Communications, relationship, coordinated management of meaning